Genome characterization of an Argentinean isolate of alfalfa leaf curl virus - Bejerman, Nicolás; Trucco, Verónica; de Breuil, Soledad; Pardina, Patricia Rodriguez; Lenardon, Sergio; Giolitti, Fabián (Archives of virology, 2018)
We investigated the molecular characteristics of an Argentinean isolate of alfalfa leaf curl virus (ALCV-Arg), a virus of the genus Capulavirus in the family Geminiviridae that was isolated from alfalfa plants showing dwarfism. The genome was found to be 2,750 nucleotides in length. In pairwise comparisons, this ALCV isolate shared 83.2% to 92.6% sequence identity with European ALCV isolates. Sequence comparisons and phylogenetic analysis showed that this isolate combines features of strains A and B of ALCV. Recombination analysis showed that ALCV-Arg is a recombinant isolate that was generated by intraspecific recombination between ALCV strains A and B. The results of this study not only show that ALCV-Arg is unique because it combines features of strains A and B but also show that ALCV naturally infects this forage crop on the American continent.